Novel polyethersulfone ultrafiltration membranes modified with Cu/titanate nanotubes. (February 2020) - Szymański, Kacper; Darowna, Dominika; Sienkiewicz, Paulina; Jose, Manu; Szymańska, Karolina; Zgrzebnicki, Michał; Mozia, Sylwia
Graphical abstract: Highlights: Improvement of PES membrane permeability by modification with Cu/TNTs. Better antifouling properties in case of lower temperature of non-solvent bath. Higher Cu content in Cu/TNTs increases water permeability but enhances fouling. Higher Cu content in Cu/TNTs improves antibacterial properties of membranes. Higher biocidal ability of Cu/TNTs-modified membranes in case of E. coli . Abstract: The influence of addition of titanate nanotubes modified with copper (Cu/TNTs) on the physicochemical, antifouling and antibacterial properties of polyethersulfone (PES) membranes obtained under various conditions is presented. The effect of polymer concentration (15 and 16 wt%) in casting dope and temperature of coagulation bath (10 and 20 °C) was investigated. Furthermore, the influence of Cu content in the Cu/TNTs (1.86 vs 12.23 wt%) on the properties of the membranes was evaluated. The physicochemical characterization of the membranes was based on scanning electron microscopy, atomic force microscopy, isoelectric point and contact angle measurements. The permeability of the mixed matrix membranes was higher compared to the neat ones, and the improvement was the most significant for 15 wt% PES content in the casting dope and Cu/TNTs with higher Cu loading. On the opposite, the best antifouling performance exhibited the membranes characterized by the lowest pure water flux (16 % PES, 10 °C) and a lower Cu content. The addition of Cu/TNTs improved the antibacterial activity of the membranes. The inhibition of the growth of Staphylococcus epidermidis was depended on the kind of Cu/TNTs used, while no significant influence in case of Escherichia coli was observed.